The efficacy of vitamin D supplementation on painful diabetic neuropathy: Protocol for a systematic review and meta-analysis. Issue 31 (31st July 2020) - Wei, Wenjing; Zhang, Yanli; Chen, Rumeng; Qiu, Xianliang; Gao, Yang; Chen, Qiu
Abstract: Background: Painful diabetic neuropathy (PDN) is one of the main and severe complications of diabetic patients, which not only accelerates the occurrence of ulcers of diabetic foot and amputation of lower extremities but also severely affects the quality of life. It is common that vitamin D deficiency in diabetic patients and especially in these patients diagnosed with diabetic peripheral neuropathy. Previous studies have proved that there is an apparent vitamin D deficiency in PDN patients, and vitamin D supplementation can effectively improve patients' pain symptoms and neurologic function. However, the evidence of these studies is unconvincing. Therefore, our research objective is to explore the effectiveness and security of vitamin D supplements on PDN. Methods: We will include randomized controlled trials on vitamin D supplementation in the treatment of PDN. And we will retrieve 8 electronic databases concerning this theme. The English databases mainly retrieve PubMed, Web of Science, Embase, and the Cochrane Library, while CNKI, VIP, CBM, and Wanfang database will be used to retrieve the Chinese Literature. There is no definite time limit for retrieval literatures, and the languages will be limited to Chinese and English. Besides, some clinical registration tests and gray literatures are also researched by us. The primary outcomes of our study are the amelioration of pain symptoms and assessment of peripheral nerve function. And some changes of biochemical indicators including fasting blood glucose, 2 hours postprandial blood glucose, glycosylated hemoglobin, calcium, and serum vitamin D level from preintervention and postintervention, adverse events will be regarded as secondary outcomes. The Review Manager RevMan5.3 will be used for meta-analysis of studies are included. Results: In this systematic review and meta-analysis, higher quality data evidence on vitamin D supplementation for PDN will be provided. Conclusion: Our study will eventually provide a proof of the efficacy and safety of vitamin D supplementation in patients with PDN, and to add a new option for the prevention and treatment of PDN patients. INPLASY registration number: INPLASY202050065